Vpliv endoskopske hemostaze na zmanjšanje umrljivosti pri bolnikih s krvavitvami iz prebavil - Skok, Pavel (Medicinski razgledi, 1996)
Endoscopy is the method of choice for localizing the site of hemorrhage and transendoscopic hemostatic procedures in patients with hemorrhage from the digestive tract. The aim of the study was to establish the mortality of patients with upper gastrointestinal bleeding and endoscopic hemostasis in our institution. The retrospective analysis includes patients who had undergone urgent endoscopic examination of the upper digestive tract and hemostatic interventions with sclerotherapy, laser photocoagulation or electrocoagulation of the hemorrhaging spot in the period between january 1994 and may 1995. 1000 patients were examined, 638 male and 362 female. In only 312 patients (31,2%) the examination revealed signs of acute or recently hemorrhage. Hemostatic interventions were performed in 275 cases. During the hospitalisation on the internal depertment 14 patients died. In 9 patients (9/275,3%) with acute hemorrhage, endoscopic hemostsis did not prove successful, therefore after seveal unsuccessfully repeated endoscopic interventios (21 in all) the patients were treated operatively. During the postoperative period, 4 patients died because of complications. Despite the development of endoscopic instruments and methods of hemostasis, mortality due to to hemorrhage from the digestive tract has not decreased essentially. Namely, numerous demanding endoscopic procedures are carried out in older patients having other diseases beside the basic one. These diseases represent the risk factors for evental surgical treatment and the following complications.
Keywords: medicina; medicine; prebavila; krvavitve